2009
DOI: 10.1295/polymj.pj2008202
|View full text |Cite
|
Sign up to set email alerts
|

Physical Aging of Photo-Crosslinked Poly(ethyl acrylate) Observed in the Nanometer Scales by Mach-Zehnder Interferometry

Abstract: Deformation in the nanometer scales of photo-crosslinked poly(ethyl acrylate) (PEA) was in situ monitored by MachZehnder interferometry (MZI). Upon irradiation with 365 nm, anthracene labeled on the PEA chains undergoes photodimerization, generating the PEA networks. The cross-link kinetics induced by different light intensities was monitored by using a UV-visible spectrometer. On the other hand, the deformation in the nanometer scales of the photocross-linked polymer was measured in situ by using a Mach-Zehnd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Owing to this inhomogeneity, a transient local strain field can be generated and developed in the sample. By performing in situ experiments using a Mach-Zehnder interferometer [51], the relaxation of this strain field in both photo-cross-linked homopolymers [45] and in the bulk state of binary polymer mixtures was reported with its consequence on the morphology emerging in photo-cross-linked polymers [52,53]. It should be noted that, in contrast to the bulk state, the effects of elastic strain are much more significant in liquid mixtures where the morphological regularity greatly decreases by periodic irradiation [54].…”
Section: Reaction-induced Elastic Strain and Its Relaxation Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…Owing to this inhomogeneity, a transient local strain field can be generated and developed in the sample. By performing in situ experiments using a Mach-Zehnder interferometer [51], the relaxation of this strain field in both photo-cross-linked homopolymers [45] and in the bulk state of binary polymer mixtures was reported with its consequence on the morphology emerging in photo-cross-linked polymers [52,53]. It should be noted that, in contrast to the bulk state, the effects of elastic strain are much more significant in liquid mixtures where the morphological regularity greatly decreases by periodic irradiation [54].…”
Section: Reaction-induced Elastic Strain and Its Relaxation Behaviormentioning
confidence: 99%
“…These results were obtained from the changes in the optical path length difference (OPLD) and in the refractive index between the irradiated and the nonirradiated parts in the same sample. Note that the strain or deformation ε induced by irradiation can be calculated from the following equation [45,51]:…”
Section: Reaction-induced Elastic Strain and Its Relaxation Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…From the plot of normalized shrinkage ( ε / ε max ) vs. non-dimensionalized elapse time deined as ( t e . k a ) where t e is the elapse time and k a is the characteristic time of the aging process, it was found that all the aging data obtained with a constant irradiation intensity can be expressed by a master curve [17].…”
mentioning
confidence: 99%